1989
DOI: 10.1088/0022-3727/22/8/036
|View full text |Cite
|
Sign up to set email alerts
|

Low-resistance silver contact on Bi-Sr-Ca-Cu-O film

Abstract: A simple method of making low-resistivity contacts ( approximately 10-7 Omega cm2) is reported for the first time on Bi-Sr-Ca-Cu-O films. The method basically involves the laying of silver-paste pads on the surface of as-deposited film, their annealing and the subsequent attachment of copper leads. The annealing step thus serves a dual purpose. It not only renders the film superconducting with requisite oxygenation but also helps in the preparation of low-resistivity contacts. The contacts on the film are quit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In our case, the grazing angle of incidence of 0.6 ° (critical angle for silver = 0.46 °) was selected to probe the Ag/YBaCuO interface. The electrical measurements were carried out by employing the three-probe configuration (Khare et al 1989) shown in figure 1, so as to obtain the contact resistance. Four-probe measurement was also made to obtain the precise R vs T data above Tc onset.…”
Section: Methodsmentioning
confidence: 99%
“…In our case, the grazing angle of incidence of 0.6 ° (critical angle for silver = 0.46 °) was selected to probe the Ag/YBaCuO interface. The electrical measurements were carried out by employing the three-probe configuration (Khare et al 1989) shown in figure 1, so as to obtain the contact resistance. Four-probe measurement was also made to obtain the precise R vs T data above Tc onset.…”
Section: Methodsmentioning
confidence: 99%